Diffusion tensor imaging, intra-operative neurophysiological monitoring and small craniotomy: Results in a consecutive series of 103 gliomas - Carrabba, Giorgio; Fiore, Giorgio; Di Cristofori, Andrea; Bana, Cristina; Borellini, Linda; Zarino, Barbara; Conte, Giorgio; Triulzi, Fabio; Rocca, Alessandra; Giussani, Carlo; Caroli, Manuela; Locatelli, Marco; et al. (Frontiers in Oncology, 2022)
Diffusion Tensor Imaging (DTI) allows visualization of the main white matter tracts while intra-operative neurophysiological monitoring (IONM) represents the gold standard for surgical resection of gliomas. In recent years, the use of small craniotomies, has gained popularity thanks to Neuronavigation and to the low morbidity rates associated with shorter surgical procedures. Aim of this study was to review a series of patients operated for glioma using DTI, IONM and tumor targeted craniotomies. The retrospective analysis included patients with supratentorial glioma who met the following inclusion criteria: pre-operative DTI, intra-operative IONM, tumor-targeted craniotomy, pre- and post-operative MRI, complete clinical charts. The DTI was performed on a 3T scanner. The IONM included electroencephalography (EEG), transcranial (TC) and/or cortical motor evoked potentials (MEP), electrocorticography (ECoG), and direct electrical stimulation (DES). Outcomes included post-operative neurological deficits, volumetric extent of resection (EOR) and overall survival (OS). One hundred and three patients (61 Males, 42 Females; mean age 54±14 years) were included and presented the following WHO histologies: 65 grade IV, 19 grade III, and 19 grade II gliomas. After 3 months, only3 patients experienced new neurological deficits. The median postoperative volume was 0cc (IQR 3). The median OS for grade IV gliomas was 15 months while fo rlow-grade gliomas it was not reached. In our experience, a small craniotomy and a tumor resection supported by IONM and DTI permitted to achieve satisfactory results in terms of neurological outcomes, EOR and OS for glioma patients.